Comparative Evaluation of Forsythiae Fructus From Different Harvest Seasons and Regions by HPLC/NIR Analysis and Anti-inflammatory and Antioxidant Assays - Qu, Qian; Li, Yuefei; Dong, Qi; Li, Shupeng; Du, Hongliang; Wang, Zhihua; Gong, Xiaopei; Zhang, Wenchang; Lv, Weijie; Chao, Limin; Liu, Mengjie; Tang, Xinggang; et al. (Frontiers in Pharmacology, 2021)
Forsythiae Fructus (FF), the dry fruit of Forsythia suspensa (Thunb.) Vahl, has a long history in traditional Chinese Medicine for heat-clearing and detoxifying. It possesses clinical therapeutic effect and biological function in different diseases. To investigate the FF difference from Henan, Shanxi and Shaanxi in August and October, the surface morphology, mid infrared, near infrared spectrum and HPLC were analyzed. Concurrently, the anti-inflammatory and antioxidant effects on LPS-induced J774A.1 cell by western blot and RT-qPCR were evaluated. The results showed that FF from different Harvest Seasons and Regions are provided with different microstructure, mid infrared and near infrared spectrum, and the levels of forsythiaside A and phillyrin of FF from Shanxi in August and phillygenin of FF from Shaanxi in August were highest. Meanwhile, FF from Shanxi and Shaanxi in August makedly reduced the levels of inflammatory cytokines and mediators (TNF-α, IL-1β, NF-κB and iNOS) and the protein expression levels of phosphorylated total IKKα/β and nuclear NF-κB. SXFF and SAXFF in August also promoted the mRNA expression levels of HO-1 and NQO1 and the protein expression levels of HO-1 and nuclear Nrf2 and suppressed the protein expression levels of KEAP1. The Spearman correlation analysis showed that phillygenin had a strong correlation with the protein expression on LPS-induced J774A.1 cell. In summary, given our results showed that FF from harvest seasons and regions contributed to the distinct differences in microstructure, mid infrared, near infrared spectrum and compound content. More importantly, FF from Shanxi and Shaanxi in August showed marked anti-inflammatory and antioxidant activities, but with some differences, which may be because different contents of phillygenin and phillyrin of lignans in FF.